Dynamic Mapping of Physical Controls for Tabletop Groupware - Fiebrink, Rebecca; Morris, Dan; Morris, Meredith Ringel (CHI '09 Proceedings of the SIGCHI Conference on Human Factors in Computing Systems, 2009)
Multi-touch interactions are a promising means of control for interactive tabletops. However, a lack of precision and tactile feedback makes multi-touch controls a poor fit for tasks where precision and feedback are crucial. We present an approach that offers precise control and tactile feedback for tabletop systems through the integration of dynamically re-mappable physical controllers with the multi-touch environment, and we demonstrate this approach in our collaborative tabletop audio editing environment. An observational user study demonstrates that our approach can provide needed precision and feedback, while preserving the collaborative benefits of a shared direct-manipulation surface. Our observations also suggest that direct touch and physical controllers can offer complementary benefits, and that providing both allows users to adjust their control strategy based on considerations including precision, convenience, visibility, and user role.